Implementation of Corporate Social Responsibility Programs At PT Sharp Electronic Indonesia - Prakoso, Sawung; Muhammad Zakaria; Setiadi, Dedy (Krisnadwipayana International Journal of Management Studies, 2023)
The background of this article is about the implementation of Corporate Social Responsibility (CSR) at PT Sharp Electronic Indonesia. This paper examines the process of implementing CSR programs. The methodology used is a qualitative literature study. In this case community and environmental empowerment is part of PT Sharp Electronic Indonesia's commitment. The results of the analysis show that the concept of CSR is indeed good, but unfortunately, until now there are still many companies that have not implemented it properly. Therefore, it is necessary to carry out an evaluation related to the implementation of the CSR Program so that the program can be implemented in a sustainable manner and can empower the community. So that in the development of the company PT Sharp Electronic Indonesia increasingly raises the pros and cons.